Influence of high fat diet and resveratrol supplementation on placental fatty acid uptake in the Japanese macaque. Issue 8 (August 2015) - O'Tierney-Ginn, P.; Roberts, V.; Gillingham, M.; Walker, J.; Glazebrook, P.A.; Thornburg, K.L.; Grove, K.; Frias, A.E.
Abstract Introduction Adequate maternal supply and placental delivery of long chain polyunsaturated fatty acids (LCPUFA) is essential for normal fetal development. In humans, maternal obesity alters placental FA uptake, though the impact of diet remains uncertain. The fatty fetal liver observed in offspring of Japanese macaques fed a high fat diet (HFD) was prevented with resveratrol supplementation during pregnancy. We sought to determine the effect of HFD and resveratrol, a supplement with insulin-sensitizing properties, on placental LCPUFA uptake in this model. Methods J. macaques were fed control chow (15% fat, n = 5), HFD (35% fat, n = 10) or HFD containing 0.37% resveratrol (n = 5) prior to- and throughout pregnancy. At ∼130d gestation (term = 173d), placentas were collected by caesarean section. Fatty acid uptake studies using 14C-labeled oleic acid, arachidonic acid (AA) and docosahexanoic acid (DHA) were performed in placental explants. Results Resveratrol supplementation increased placental uptake of DHA (P < 0.05), while HFD alone had no measurable effect. Resveratrol increased AMP-activated protein kinase activity and mRNA expression of the fatty acid transporters FATP-4, CD36 and FABPpm (P < 0.05). Placental DHA content was decreased in HFD dams; resveratrol had no effect on tissue fatty acid profiles. Discussion Maternal HFD did not significantly affect placental LCPUFA uptake. Furthermore, resveratrol stimulated placental DHA uptake capacity, AMPK activation and transporter expression. Placental handling of DHA is particularly sensitive to the dramatic alterations in the maternal metabolic phenotype and placental AMPK activity associated with resveratrol supplementation.